Evaluation of Thermographic Imaging in Canine Hindlimb Muscles After 6 Min of Walking—A Pilot Study - Repac, Jennifer; Alvarez, Leilani X.; Lamb, Ken; Gillette, Robert L. (Frontiers in Veterinary Science, 2020)
Abstract Objective: To evaluate changes in superficial temperature of hindlimb muscles before and after a 6-minute walk in healthy dogs. Methods: Two infrared thermographic images were captured of the proximal and distal hindlimbs of 11 healthy dogs before and after a 6-minute walk. Orthopedic exam and objective gait analysis confirmed the healthy status of study subjects. Superficial temperatures of the gastrocnemius, biceps femoris, and gracilis were assessed. Analysis of images was performed using 2 different methods of region of interest (ROI) selection. ROI were selected first using one point (single pixel) in the muscle and then separately by selecting a line (LN) corresponding to many points of each muscle belly from which an average was taken. P < 0.05 was considered significant. Results: There was no significant change in temperature using point ROI before and after 6 minutes of walking of the gastrocnemius, gracilis, and biceps femoris muscles (p=0.273, p=0.349, p=0.351, respectively). Using linear ROI, both biceps femoris and gracilis muscles exhibited significant increases in temperature (p <0.0001, p = 0.032 respectively). There was no significant increase in temperature of gastrocnemius muscle for both point and linear ROI selection (p= 0.273, p= 0.448 respectively). The right biceps femoris temperatures were higher compared to left biceps femoris using the linear ROI before and after walks (p < 0.0001). The average standard deviation of point selected values were greater than LN selected values of the biceps femoris (1.35 and 1.11) and gastrocnemius (1.51 and 1.23). In contrast, the gracilis muscle demonstrated decreased standard deviation using point selection versus LN selection (1.09 and 1.3). Conclusions: The biceps femoris and gracilis muscles demonstrated significant increases in surface temperature after 6 minutes of walking using the linear method of ROI. Measurement of numerous points along the entire length of each evaluated muscle may provide a more accurate assessment of the increased vascularity within the tissues resulting from work compared to single point selection. Clinical significance: Prior activity and ROI selection method should be considered when interpreting thermography results.